Hybridization of papain molecules and DNA-wrapped single-walled carbon nanotubes evaluated by atomic force microscopy in fluids - Masaki Kitamura; Kazuo Umemura (Scientific Reports, 2023)
Abstract Although various conjugates of single-walled carbon nanotubes (SWNTs) and biomolecules, such as nanobiosensors and nanobiodevices, have been reported, the conjugation of papain and SWNTs have not been reported because of the formation of unexpected aggregates. In this study, atomic force microscopy (AFM) in liquid was used to investigate the interactions between papain and DNA-wrapped SWNTs (DNA–SWNTs) at two different pH values (pH 3.0 and 10.5). The direct AFM observation of the mixture of papain and DNA–SWNTs confirmed the aggregation of papain molecules with DNA–SWNTs in the buffer solutions. The numerous and non-uniform adsorption of papain molecules onto DNA–SWNTs was more pronounced at pH 3.0 than that at pH 10.5. Furthermore, thick conjugates appeared when papain and DNA–SWNTs were simultaneously mixed. The near-infrared photoluminescence spectra of the SWNTs drastically changed when the papain molecules were injected into the DNA–SWNT suspension at pH 3.0. Thus, the regulation of electrostatic interactions is a key aspect in preparing optimal conjugates of papain and DNA–SWNTs. Furthermore, although previous papers reported AFM images of dried samples, this study demonstrates the potential of AFM in liquid in evaluating individual bioconjugates of SWNTs.